Description and initial evaluation of incorporating electronic follow-up of study participants in a longstanding multisite cohort study. Issue 1 (December 2016) - Kershaw, Kiarri; Liu, Kiang; Goff, David; Lloyd-Jones, Donald; Rasmussen-Torvik, Laura; Reis, Jared; Schreiner, Pamela; Garside, Daniel; Sidney, Stephen
Abstract Background The objective of this study was to evaluate a pilot program that allowed Chicago field center participants of the Coronary Artery Risk Development in Young Adults (CARDIA) study to submit follow-up information electronically (eCARDIA). Methods Chicago field center participants who provided email addresses were invited to complete contact information and follow-up questionnaires on medical conditions electronically in 2012–2013. Sociodemographic characteristics were compared between those who did and did not complete follow-up electronically. The number of participant contacts by CARDIA staff needed before follow-up was completed was also evaluated. Results Blacks and low socioeconomic position individuals were less likely to complete follow-up using the electronic questionnaire. Participants who used the electronic questionnaire for follow-up needed fewer contacts (e.g., median 1 contact compared with 3for contact information follow-up), but they also needed fewer contacts prior to eCARDIA (median 1 before and after eCARDIA). Conclusions Findings suggest other approaches will be needed to maintain contact and elicit follow-up information from harder-to-reach individuals.